The relationship between sprint speed and sprint motion in amputee soccer players - Miyamoto, Aya; Maehana, Hirofumi; Yanagiya, Toshio (European Journal of Adapted Physical Activity, 2019)
Sprint performance plays an important role in amputee soccer. Sprint motion such as step length and frequency are generally accepted as one of the determining factors of sprint performance. However, there is a paucity of sprint motion studies. Here we sought to analyze sprint motion in outfield positioned amputee soccer players using crutches and to clarify the relationship between sprint speed and sprint motion. Twelve male Japanese outfield players participated; they performed a 30-m sprint with maximum effort. Sprint times and speeds were recorded using electronic timing gates. A high-speed video camera recorded sprint motion. The time and distance of each crutch and step were determined via image analysis. Sprint speed was significantly positively correlated with body mass (r=0.692, p=0.013), length and frequency of one running cycle(r=0.817, p=0.001; r=0.666, p=0.018, respectively), 1st-2nd step length (r=0.890, p=0.001), and crutch-1st step length (r=0.659, p=0.020). In addition, sprint speed was significantly negatively correlated with time taken for each 10-m interval as well as with contact time of first foot (r=-0.881, p=0.001) and crutch stance time (r=-0.670, p=0.017). Our results suggest that improving sprint speed requires increasing the step length within a shorter time frame in first foot step and crutch stance.
Keywords: sprinting; soccer; disability; high-speed camera